Tahapan Teknik Menggambar Ragam Hias Nusantara dengan Program Komputer Autocad - Ulli Aulia Ruki; Budi Setiawan (Bina Nusantara University, 2013)
Nowadays, technology has developed in many different disciplines. One of the technologies that have been used in design interior is AutoCAD software used in technical drawing. This AutoCAD software has been well-known by drafters. Advantages of this software are small period time of working, drawing with precisely measurement; and it is environmental friendly because it uses digital data that can reduce paper use. Drawing decorative ornament is one of difficulties that have been avoided by students to draw. Therefore the purpose of this article is to give information about steps of drawing decorative element using AutoCAD for their technical drawing in interior design. The article used literature study and website of professional institutions about AutoCAD as an additional source to be explanations about pattern of each ornament. Results of using this technique in AutoCAD will minimize time consuming, and it will help students draw the Indonesian archipelago decorative ornament.